Mechanistic insights into the key marine dimethylsulfoniopropionate synthesis enzyme DsyB/DSYB. Issue 2 (15th June 2022) - Li, Chun‐Yang; Crack, Jason C.; Newton‐Payne, Simone; Murphy, Andrew R. J.; Chen, Xiu‐Lan; Pinchbeck, Benjamin J.; Zhou, Shun; Williams, Beth T.; Peng, Ming; Zhang, Xiao‐Hua; Chen, Yin; Le Brun, Nick E.; et al.
Abstract: Marine algae and bacteria produce approximately eight billion tonnes of the organosulfur molecule dimethylsulfoniopropionate (DMSP) in Earth's surface oceans annually. DMSP is an antistress compound and, once released into the environment, a major nutrient, signaling molecule, and source of climate‐active gases. The methionine transamination pathway for DMSP synthesis is used by most known DMSP‐producing algae and bacteria. The S ‐directed S ‐adenosylmethionine (SAM)‐dependent 4‐methylthio‐2‐hydroxybutyrate (MTHB) S ‐methyltransferase, encoded by the dsyB/DSYB gene, is the key enzyme of this pathway, generating S ‐adenosylhomocysteine (SAH) and 4‐dimethylsulfonio‐2‐hydroxybutyrate (DMSHB). DsyB / DSYB, present in most haptophyte and dinoflagellate algae with the highest known intracellular DMSP concentrations, is shown to be far more abundant and transcribed in marine environments than any other known S ‐methyltransferase gene in DMSP synthesis pathways. Furthermore, we demonstrate in vitro activity of the bacterial DsyB enzyme from Nisaea denitrificans and provide its crystal structure in complex with SAM and SAH‐MTHB, which together provide the first important mechanistic insights into a DMSP synthesis enzyme. Structural and mutational analyses imply that DsyB adopts a proximity and desolvation mechanism for the methyl transfer reaction. Sequence analysis suggests that this mechanism may be common to all bacterial DsyB enzymes and also, importantly, eukaryotic DSYB enzymes from e.g., algae that are the major DMSP producers in Earth's surface oceans. Impact statement: Dimethylsulfoniopropionate (DMSP) is one of Earth's most abundant organosulfur‐containing molecules which influence marine nutrient cycling, chemotaxis, atmospheric chemistry, and potentially the climate. This study provides the first structural and mechanistic understanding of the key DMSP synthesis enzyme in marine bacteria (DsyB) and algae (DSYB) that are responsible for the annual production of 8 billion tonnes of DMSP. DsyB is the first DMSP synthesis enzyme to be analyzed at the structural and mechanistic level. This study defines the functional characteristics of the DsyB/DSYB enzyme family that has a central role in driving the marine microbial cycling of organosulfur.